Surgical implants. Specification for the dimensions of intramedullary nails of clover leaf and V-shaped cross section made of stainless steel or cobalt-chromium-tungsten-nickel alloy and dimensions of extraction hooks Part 19, (30th June 1986) - British Standards Institution,
No abstract available